UK Fleet Operators Failing to Implement Basic Road Safety Policies - Will Murray (Journal of Road Safety, 2005)
There has been an increasing amount of discussion on fleet safety in the UK in recent months, in part caused by the proposed Corporate Manslaughter and Road Safety Bills, as well as changes to Police and HSE reporting requirements on fleet vehicles. Recent research studies in the UK have focused specifically on the fleet safety policies that organisations have in place. Towards the end of 2004, Nottingham Business School’s Centre for Automotive Industries management found that only 31% of the fleets in its survey had a written fleet safety policy in place. A study by the Royal Automobile Club in early 2005 put this figure at 60% of fleets More recent findings published on the internet suggest that 79% of companies have no fleet risk management strategy in place.